Lipomics: A Potential Carrier for the Intravenous Delivery of Lipophilic and Hydrophilic Drugs - David Ramírez-Hernández; Carlos Juárez-Osornio; Vanessa Izquierdo-Sánchez; Pavel A. Figueroa-Rodríguez; Jorge Organista-Nava; Yazmín Gómez-Gómez; Luis Alberto Medina (MDPI AG, 2022)
In the present work, we propose the development of a novel carrier that does not need organic solvents for its preparation and with the potential for the intravenous delivery of lipophilic and hydrophilic drugs. Named lipomics, this is a mixed colloid of micelles incorporated within a liposome. This system was designed through ternary diagrams and characterized by physicochemical techniques to determine the particle size, zeta potential, shape, morphology, and stability properties. The lipomics were subjected to electron microscopy (SEM, TEM, and STEM) to evaluate their physical size and morphology. Finally, pharmacokinetic studies were performed by radiolabeling the lipomics with Technetium-99m chelated with BMEDA to evaluate the in vivo biodistribution through techniques of molecular imaging (microSPECT/CT) in rats. Radiolabeling efficiency was used to compare the encapsulation efficiency of the hydrophilic and lipophilic molecules in lipomics and liposomes. According to the results, lipomics are potentially carriers of lipophilic and hydrophilic drugs.